Analyzing forces in swimming with Aquanex
Aquanex is a computerized system for measuring forces in an aquatic environment. - Aquanex can be used with all four competitive swimming strokes. - Aquanex provides a thorough analysis of the forces exerted during swimming. - Aquanex is a valuable diagnostic tool for all types of competitive swimmers.